PENGARUH KUALITAS PELAYANAN DRIVER GRABCAR TERHADAP KEPUASAN WISATAWAN NUSANTARA DI BADUNG, BALI - Sarfina, Eminilda; Sendra, I Made; Sudana, I Putu (Jurnal IPTA (Industri Perjalanan Wisata); Vol 11 No 2 (2023): Jurnal IPTA (December 2023), 2023)
GrabCar is an internet-based transportation service that can be accessed through an online application that rejuvenates users/tourists, but there are some complaints from users or tourists when using GrabCar. The purpose of this study is to determine the effect of GrabCar Driver service quality on the satisfaction of domestic tourists in Badung Regency, Bali. The operational definition of variables used in this study is X, Y and characteristics. The sampling technique uses accindental sampling with a total of 100 respondents, namely domestic tourists who have used GrabCar in Badung Regency, Bali. Data collection techniques are carried out by observation, questionnaires, interviews, literature studies, and documentation. This research is quantitative descriptive by using simple linear regression analysis as data analysis. This study uses descriptive data analysis which is processed using the SPSS 25.0 application for windows. The results of simple linear regression analysis through partial testing of the effect of variable X on Y show that the t test obtains a significant value of 0.000 <0.005, which means that the service quality variable has a positive effect on tourist satisfaction. The R square determinant coefficient value is 0.630, service quality affects domestic tourist satisfaction, while the remaining 37% is influenced by other variables such as competition variables, price variables, trust variables, for the Grab manager must improve facilities, maintain the company's image, hospitality to tourists/ passengers, and improve CHSE standards.